Infância e memória: uma reflexão sobre questões étnico-raciais na educação infantil - Silva, Geice Nogueira da (Universidade Federal do Tocantins, 2022)
The object that guided our research emerged in 2018, in the discipline Childhood, Culture and Society. It gained support from the experiences in the Institutional Scholarship and Initiation to Teaching Program (PIBID); and Supervised Internship of the Initial Years, in 2018/2019. Thus, in our first section we trace a brief history of the process of racism in Brazil, resulting from the slavery period and its implications for ethnic-racial identity, in the post-abolition period (1888). Then we investigate the contributions of Law 10.639/2003 and the main guidelines that guide Early Childhood Education in Brazil, about ethnic-racial issues. In the third section, we turn to childhood memories, relating them to the records of pedagogical experiences with the PIBID and the Supervised Internship of the Initial years. The records showed that some black children were not identifying with their Afro-Brazilian characteristics. Thus, in our methodology, we resort to the concept of memory, as a qualitative research method, which is influenced by the social environment to conclude that anti-racist pedagogical actions are fundamental in the production of new subjectivities that enable the ethnic-racial identity of subjects at school.